2005
DOI: 10.1007/s11104-005-0263-6
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Root Diameter, Tree Age, Soil Depth and Season on Fine Root Survivorship in Prunus avium

Abstract: The rapid turnover of the fine root system is a major pathway of carbon and nutrient flow from plant to soil in forest ecosystems. In order to quantify these fluxes there is a need to understand how fine root demography is influenced by edaphic, environmental and plant ontogenetic factors. We studied the influence of four major factors (season, depth, root diameter and tree age) on the survivorship and longevity of fine roots of Prunus avium L. (wild cherry) over two years in North East Scotland. Survival anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
87
1
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 39 publications
(39 reference statements)
14
87
1
8
Order By: Relevance
“…However, the variation in the total production and turnover rates from year to year has generally been recorded within a single tree species and/or stand (Burke and Raynal 1994;Rytter 2013;Leppälammi-Kujansuu et al 2014), and the interannual variability in the fine root turnover rate was equal to or greater than the difference among species obtained for some temperate tree species (McCormack et al 2014). In addition, soil depth could also have a major influence on the fine root dynamics of shrubs (Aerts et al 1989;Baddeley and Watson 2005). Therefore, the long-term trend requires further study to identify the average variation in the annual production and turnover rates along the soil profile among the studied shrub species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the variation in the total production and turnover rates from year to year has generally been recorded within a single tree species and/or stand (Burke and Raynal 1994;Rytter 2013;Leppälammi-Kujansuu et al 2014), and the interannual variability in the fine root turnover rate was equal to or greater than the difference among species obtained for some temperate tree species (McCormack et al 2014). In addition, soil depth could also have a major influence on the fine root dynamics of shrubs (Aerts et al 1989;Baddeley and Watson 2005). Therefore, the long-term trend requires further study to identify the average variation in the annual production and turnover rates along the soil profile among the studied shrub species.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the investigated species are evergreen, whereas the other three species are deciduous. Although soil depth could have a major influence on fine root dynamics due to the variations in soil microenvironment (Aerts et al 1989;Baddeley and Watson 2005), shallow roots were responsible for the majority of total annual fine root production and mortality (Hendrick and Pregitzer 1996). Therefore, we focused on the fine roots in top soil layer in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other authors also found this strong dependence of root survivorship on root diameter (Gill and Jackson 2000;Wells and Eissenstat 2001;King 1,050, 1,540, 1,890 m a.s.l. 1,890, 2,380, 3, et al 2002;Baddeley and Watson 2005). This may be explained by higher nutrient concentrations and respiration rates of small diameter roots, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that the season (or time) of emergence can alter fine-root life span (e.g. Tingey et al, 2000;Ponti et al, 2004; Table 1), as can tree age (Copeland, 1952;Baddeley and Watson, 2005). The categorization according to micro-size root diameter revealed that thinner fine roots tended to have shorter life spans than thicker fine roots (Wells and Eissenstat, 2001;Baddeley and Watson, 2005).…”
Section: Qualitative Variation Among "Fine Roots"mentioning
confidence: 99%
“…Tingey et al, 2000;Ponti et al, 2004; Table 1), as can tree age (Copeland, 1952;Baddeley and Watson, 2005). The categorization according to micro-size root diameter revealed that thinner fine roots tended to have shorter life spans than thicker fine roots (Wells and Eissenstat, 2001;Baddeley and Watson, 2005). The diameter of 'fine roots' can also differ along root branching orders: roots with an apex (root tip) are thinner than the axis roots to which they are attached (Pregitzer et al, 2002;Guo et al, 2004), suggesting shorter life spans in thinner apical roots.…”
Section: Qualitative Variation Among "Fine Roots"mentioning
confidence: 99%